Historical Ecological Value in Banyubiru Folklore and Its Contribution to the Development of Natural Ecotourism Conservation - Lailatul Fitriyah (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
Folklore as a tradition of a community group that is passed down from generation to generation certainly implies various kinds of social and moral values. One of them is folklore about Banyubiru that contribute to shaping the understanding and responbility of the Sumberejo Village community to the wisdom of the surrounding environment. So, an interesting value to be studied in foklore is the value of historical ecology and its role in the development of nature ecotourism conservation. The method used is a qualitative research method with data collection through observation, documentation, and direct interviews. The results of this study showed that folklore Banyubiru contain ecological values, such as the values of respect for nature and its living creatures and conservation values. These ecological values need to be understood by the local community as a form of its role in supporting the development of conservation, especially in this case is to maintain the existence Banyubiru as one of the natural ecotourism that must be preserved. Therefor, through the study of ecology in folklore, i tis expected that community can interpret it correctly by implying it in the conservation efforts of the bath complex and the flora and fauna in it as a strategy for the sustainability of natural ecotourism.